Knock at Midnight: Fear, Resilience and the Female Medical Journey - Ali, Hamna (Journal of Pakistan Psychiatric Society, 2026)
This essay explores the fear, vulnerability, and resilience shaping the experiences of women in medicine through the parallel stories of a resident facing danger during night duty, and a medical student struggling with anxiety and burnout. Set against the realities of workplace violence, harassment, and emotional strain, the essay argues that female medical professionals must navigate both personal and structural barriers. It concludes that resilience alone is insufficient without institutional reform, collective support, and stronger protections to ensure women in medicine can work and learn safely.